2020
DOI: 10.1089/jwh.2019.7769
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Associations Between Informal Caregiving and Wellbeing in Low- and Middle-Income Countries

Abstract: Background: Health risks among informal caregivers have received inadequate attention in low and middle income countries. We examined cross-sectional data from 28611 adults 18 years and older in Ghana, India, Mexico, Russia and South Africa in the WHO Study on Global AGEing and Adult Health (SAGE) to examine gender differences in informal caregiving and wellbeing. Methods: Wellbeing was measured by self-rated health, difficulties with tasks, self-reported and diagnosed depression and anxiety. Informal caregivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
2
18
2
1
Order By: Relevance
“…Recent research suggests that, in the context of low- and middle-income countries, there are differences in the prominence and manifestation of caregiver burden between men and women. 35 Although clear gender differences were not evident in our study, this may in part be because of the overlaying multi-faceted high burden experienced by most participants. In Africa, caregiving is seen as a predominantly female practice, though this may be changing.…”
Section: Discussioncontrasting
confidence: 62%
“…Recent research suggests that, in the context of low- and middle-income countries, there are differences in the prominence and manifestation of caregiver burden between men and women. 35 Although clear gender differences were not evident in our study, this may in part be because of the overlaying multi-faceted high burden experienced by most participants. In Africa, caregiving is seen as a predominantly female practice, though this may be changing.…”
Section: Discussioncontrasting
confidence: 62%
“…Nevertheless, the phenomenological emphasis of this study uncovered the extent to which income is still controlled by men within the family and suggests that more provision needs to be made for the caring work and household maintenance that frequently falls on sisters and women. 17,24 The impact of stigma on siblings is particularly evident in the findings of this study, supporting research that points to the high overall degree of perceived stigmatisation of mental illness in South Africa 25 and other parts of Africa. 26 The participants in this study reported remaining silent in the face of stigma within their communities, experiencing shame and embarrassment in line with the international findings.…”
Section: Discussionsupporting
confidence: 79%
“…Although the sixth latent profile was rather small (0.5% of the sample), it seemed to represent persons with intensive home care duties and fewer work hours per day. This profile might reflect informal caregivers, who report worse mental health than non-carers and thus are of relevant target groups for prevention [ 24 , 25 ]. Therefore, we chose the model with six latent profiles for further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…However, mothers report less happiness, more stress and greater fatigue than fathers when asked about time spent with their children [ 23 ]. Beyond childcare, if a relative or close person is unwell, it also mainly falls to women to take care of them; although both male and female carers report worse mental health than non-carers [ 24 , 25 ]. Interestingly, housework appeared to be a stress relief to female but not male caregivers [ 25 ].…”
Section: Introductionmentioning
confidence: 99%